Efforts to Increase Faith and Immunity of the Solokuro Village Community Through Health Seminars: Upaya Peningkatan Iman dan Imun Masyarakat Desa Solokuro Melalui Seminar Kesehatan - Romadhoni , Zaidan Aufi; Cholifah (Procedia of Social Sciences and Humanities, 2022)
Social Service activities in the form of health seminars in order to strengthen faith and immunity to realize a truly healthy society of spiritual body. This activity was carried out in Solokuro village of Solokuro district of Lamongan district on February 28, 2022. The purpose of this activity is to realize a healthier life of the spiritual body through the process of strengthening faith and immunity. From this activity it is known that the community is more enthusiastic in improving a healthy lifestyle by maintaining immunity as described in islamic sharia. The method used in this activity is to gather the public to attend health seminars, then continued with free health check activities designed using strict health protocols. The enthusiasm of the community in following health checks is also very high, with the age range of adolescent, adult, and elderly participants amounting to 135 participants. The stimulation received by the community to maintain endurance and immunity can be responded to properly, thus providing hope for the realization of a healthy social life and avoiding all kinds of diseases, especially from the transmission of the Covid-19 virus.